Idiopathic hypokalemic periodic paralysis: A series of cases clustered in a part of Eastern India - Mukherjee, Joydeep; Chakraborty, Durga Prasad; Sinharoy, Uma; Saha, Shankar Prasad (Asian Journal of Medical Sciences, 2015)
Background: Most of the studies on hypokalemic periodic paralysis (HOPP) in India and abroad had described secondary causes as the origin of the disease. We had observed a series of HOPP cases clustered within 40 kilometers around Bankura, a district town of West Bengal, Eastern India. The aim of our study was to probe into the clinical, biochemical and electrophysiological details of the cases, which were found to be idiopathic. Material and Methods: 32 idiopathic HOPP cases, attending the neurology OPD or admitted in Bankura Sammilani Medical College & Hospital (BSMCH), were selected from October 2006 to May 2008. All the secondary causes of HOPP were excluded. The patients were evaluated and the data was analyzed. Results: Cases were clustered within a 40-kilometer radius from Bankura town, location of BSMCH. Male: female = 4.3:1. Median age of onset was 23.5 years (4-50 years). Median number of attacks was 2.5, (1 to 70); duration 3 hours - 6 days, median 3 days. Strenous physical activity was most common precipitating factor. 25% had bulbar symptoms, 9.4% had bladder dysfunction and 46.9% had diminished to absent deep tendon reflexes. Mean serum potassium = 2.45 mEq/L (1.4 – 3.1 mEq/L). Conclusion: We had observed a group of idiopathic HOPP cases within a relatively small area in a short span of time in contrast to most other Indian studies, where the share of idiopathic aetiology is comparatively smaller. This underscores the importance of a larger study with genetic analysis on the aetiology of the idiopathic HOPP in this area. DOI: http://dx.doi.org/10.3126/ajms.v6i6.12482 Asian Journal of Medical Sciences Vol.6(6) 2015 83-87